2019
DOI: 10.3390/app9010179
|View full text |Cite
|
Sign up to set email alerts
|

Truth and Myths about 2D Tensegrity Trusses

Abstract: The concept of tensegrity is understood in many ways. This term is often improperly used for structures that have some, but not necessarily the key, tensegrity properties. The concept of tensegrity systems is misused in reference to both mathematical models and completed engineering structures. The aim of the study is to indicate which of the plane (2D) trusses presented in the literature are erroneously classified as tensegrities. Singular value decomposition of the compatibility matrix and spectral analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…Subsequent workers-after Fuller and Snelson-have sought to provide more precise definitions of what constitutes a viable tensegrity structure, bringing in additional considerations, such as the requirement that there exist a state of self-stress, or that there must exist infinitesimal mechanisms, resisted by self-stress forces. For example, on the basis of the latter, Obara et al (2019) have suggested that Snelson's well-known X-shaped module (comprising two diagonal struts compressed via a cable ring, Snelson (1965)) should not be considered as a true tensegrity. However, it should be borne in mind that when seeking to optimize a given problem, the more considerations (or 'constraints') that are included, the higher the objective function is likely to be.…”
mentioning
confidence: 99%
“…Subsequent workers-after Fuller and Snelson-have sought to provide more precise definitions of what constitutes a viable tensegrity structure, bringing in additional considerations, such as the requirement that there exist a state of self-stress, or that there must exist infinitesimal mechanisms, resisted by self-stress forces. For example, on the basis of the latter, Obara et al (2019) have suggested that Snelson's well-known X-shaped module (comprising two diagonal struts compressed via a cable ring, Snelson (1965)) should not be considered as a true tensegrity. However, it should be borne in mind that when seeking to optimize a given problem, the more considerations (or 'constraints') that are included, the higher the objective function is likely to be.…”
mentioning
confidence: 99%
“…By solving the system of equations obtained by the equilibrium conditions embodied in Equations (22) and (23) for each of the n geometrical configurations, the magnitudes of the forces…”
Section: Methodology Proposedmentioning
confidence: 99%
“…This section presents the numerical examples used to corroborate and compare the results obtained from the static analysis using Equations (22) and (23) and static analysis using ANSYS c . Four different cases were reviewed, choosing values of the joint variables for positions within the workspace of the tensegrity robot.…”
Section: Numerical Experimentsmentioning
confidence: 99%
See 2 more Smart Citations